Efektivitas Pengelolaan Alokasi Dana Desa (ADD) di Negeri Amahusu Kecamatan Nusaniwe Kota Ambon - Aknes Melani Nunumete; Zainal Abidin Rengifurwarin; Hendry Selanno (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to analyze and describe the effectiveness of Village Fund Allocation (ADD) management, as well as the supporting and inhibiting factors in Negeri Amahusu, Nusaniwe District, Ambon City. The research employs a qualitative method with in-depth interview techniques for data collection.Based on the findings, it can be concluded that the management of Village Fund Allocation (ADD) in Negeri Amahusu is transparent, but community participation needs to be improved through more effective socialization and communication. The use of ADD aligns with the planned budget, yet challenges persist in fund disbursement and transparency in proposal acceptance. Financial administration is carried out accountably, despite encountering technical difficulties in transaction recording. The capacity of village officials still requires improvement, particularly in understanding updated regulations and financial reporting. Community participation is relatively high in village meetings and mutual cooperation activities, although material contributions remain limited. Coordination between institutions functions effectively, yet formal communication must be enhanced to ensure clearer information dissemination and greater community involvement.